2017
DOI: 10.1097/iae.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Outcomes of Intravitreal Bevacizumab for Choroidal Neovascularization in Patients With Pathologic Myopia

Abstract: The significant correlation between the BCVA at 6 years and the size of the macular atrophy indicates that treatments to prevent the development of macular atrophy are important for the long-term visual outcome in eyes with active CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Anti-VEGF therapy is the first-line therapy for mCNV, because the effect of PDT, which is an effective treatment for AMD, is limited to maintaining vision due to the high rate of CRA progression [5,23,24]. However, several investigators have reported that the VA improved significantly from baseline just after treatment, was maintained for 3 or 4 years, then declined slightly thereafter mainly due to CRA progression [6][7][8][9][10][11][12]. Oishi et al evaluated the long-term outcomes in 22 eyes with mCNV after intravitreal injection of bevacizumab (IVB) (Avastin, Genentech) for at least 4 years [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-VEGF therapy is the first-line therapy for mCNV, because the effect of PDT, which is an effective treatment for AMD, is limited to maintaining vision due to the high rate of CRA progression [5,23,24]. However, several investigators have reported that the VA improved significantly from baseline just after treatment, was maintained for 3 or 4 years, then declined slightly thereafter mainly due to CRA progression [6][7][8][9][10][11][12]. Oishi et al evaluated the long-term outcomes in 22 eyes with mCNV after intravitreal injection of bevacizumab (IVB) (Avastin, Genentech) for at least 4 years [9].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term visual prognosis is poor without treatment [4]. Although various treatments, including laser photocoagulation, macular translocation, surgical CNV removal, photodynamic therapy (PDT), and anti-vascular endothelial growth factor (anti-VEGF) therapy, have been performed [5], the long-term visual outcomes are extremely poor primarily due to the development of chorioretinal atrophy (CRA) around the regressed CNV [6][7][8][9][10][11][12]. To improve the long-term visual outcomes of mCNV, treatments are needed that also prevent development of CRA.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of IVR for mCNV have been demonstrated in several small prospective and retrospective studies (19)(20)(21)(22). There are a few reports on longterm outcomes of anti-VEGF therapy in mCNV in the literature (23)(24)(25). The aim of this study was to report the long-term anatomical and visual outcomes of IVR monotherapy in naive CNV caused by myopia.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] Previously, the standard treatment option for myopic CNV is photodynamic therapy (PDT); however, the patients treated with PDT have limited long-term visual outcomes. [4] Recently, anti-vascular endothelial growth factor (anti-VEGF) drugs such as ranibizumab, [5][6] bevacizumab, [7] and aflibercept [8] have been used to treat myopic CNV with promising results. The study of PDT versus intravitreal bevacizumab (IVB) provided evidence for the superiority of intravitreal bevacizumab over 3 PDT in treating myopic CNV.…”
Section: Introductionmentioning
confidence: 99%